2020
DOI: 10.21203/rs.3.rs-55406/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphometric study of suprascapular notch and scapular dimensions in Ugandan dry scapulae with specific reference to the incidence of completely ossified superior transverse scapular ligament

Abstract: Background: Understanding of suprascapular notch (SSN) anatomy and relationship with scapular dimensions are vital in diagnosis, prevention, and assessment of suprascapular nerve entrapment syndrome. The study aimed to assess morphometry of suprascapular notch and scapular dimensions in Ugandan dry scapulae with specific reference to scapulae with completely ossified superior transverse scapular ligaments. Methods: This was a cross-sectional analytical study conducted on 50 Ugandan dry scapulae. SSN types and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…2010 in Kenya who reported 4 scapulae (2.9%) and Adewale et al . 2020 in Uganda who reported 10 scapulae (8%), the incidence rate of the current study is generally smaller [ 3 , 11 ]. However, the rate of complete ossification of the suprascapular ligament in this study was higher than that reported by Natsis et al .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…2010 in Kenya who reported 4 scapulae (2.9%) and Adewale et al . 2020 in Uganda who reported 10 scapulae (8%), the incidence rate of the current study is generally smaller [ 3 , 11 ]. However, the rate of complete ossification of the suprascapular ligament in this study was higher than that reported by Natsis et al .…”
Section: Discussionmentioning
confidence: 77%
“…The current study examined the morphology and morphometric dimensions of the suprascapular notch in adult Malawian cadavers and their clinical implications associated with complete ossification of the suprascapular ligament. Numerous studies reported on the variations of the morphology and morphometric dimensions of the suprascapular notch in various populations [ 11 , 13 , 14 ]. These dimensional variations are population specific and may be attributed to genetic, environmental and regional differences [ 9 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En numerosos artículos, relatos de casos y casos clínicos, en diferentes individuos de diversos países, se ha reportado la completa osificación del ligamento transverso superior de la escápula, así se ha reportado en: americanos (Ticker et al, 1998); turcos (Büyükmumcu et al, 2013); nigerianos (Osuagwu et al, 2005), en sujetos de India (Khan, 2006); en brasileños (Silva et al, 2007); pakistaníes (Zahid et al, 2014;kenianos (Sinkeet et al, 2010); ugandeses (Adewale et al, 2020), entre otros. Por otra parte, se han descrito dos forámenes escapulares en un mismo hueso (Covantev et al, 2016).…”
Section: Introductionunclassified